2021
DOI: 10.7759/cureus.16420
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sociodemographic Parameters With Depression, Anxiety, Stress, Sleep Quality, Psychological Trauma, Mental Well-Being, and Resilience During the Second Wave of COVID-19 Pandemic: A Cross-Sectional Survey From India

Abstract: This study was conducted to assess the traumatic impact of the second wave of coronavirus disease 2019 (COVID-19) pandemic on depression, anxiety, stress, sleep quality, mental well-being, and resilience among the general population of India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 26 publications
(27 reference statements)
2
24
1
Order By: Relevance
“…The prevalence of any kind of stress was reported to be higher almost in all the studies. [ 26 27 28 ] In a study conducted by Kaur et al , 2021,[ 28 ] 22% reported stress symptoms which are similar to our findings during lockdown-1 where 21.54% of the participants reported to being stressed due to COVID-19. Due to an increase in the prices of essential commodities like food and decreased food availability, panic attacks, sudden increase or decrease in appetite and insomnia were reported in many studies.…”
Section: Discussionsupporting
confidence: 84%
“…The prevalence of any kind of stress was reported to be higher almost in all the studies. [ 26 27 28 ] In a study conducted by Kaur et al , 2021,[ 28 ] 22% reported stress symptoms which are similar to our findings during lockdown-1 where 21.54% of the participants reported to being stressed due to COVID-19. Due to an increase in the prices of essential commodities like food and decreased food availability, panic attacks, sudden increase or decrease in appetite and insomnia were reported in many studies.…”
Section: Discussionsupporting
confidence: 84%
“… 5 Hospitals were struggling to function to their full potential due to insufficient resources such as low oxygen supply, non-availability of beds, increasing deaths, also the media was reporting stories of panic everywhere. 6 The patients who tested positive, their family members, the patients who recovered from Covid-19 and citizens experienced psychological distress. 7 , 8 Covid-19 patients complained about sleep disturbances due to a long period of isolation, suffering, illness relapse threat, and being infectious for others.…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 8 Covid-19 patients complained about sleep disturbances due to a long period of isolation, suffering, illness relapse threat, and being infectious for others. 6 …”
Section: Introductionmentioning
confidence: 99%
“…Studies included in our meta-analysis are shown in Table 1 . [ 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 ] All 22 included studies were conducted using online cross-sectional surveys using the snowball sampling technique by distributing the Google form through Facebook, WhatsApp, or Twitter. In 16 of 22 studies, the online survey was conducted across India, while in others, it was conducted in selected states/states.…”
Section: R Esultsmentioning
confidence: 99%